INTRODUCTION OF BREAK EVEN POINT (BEP) ANALYSIS AS STOCK FOR STUDENTS OF FOOD SCIENCE AND TECHNOLOGY IN GROWING THE ENTREPRENEURIAL SOUL - Utami, Suci Nur; Adita, M. Dini (RANDANG TANA - Jurnal Pengabdian Masyarakat, 2019)
Break Even Point Analysis (BEP) is one of the tools in economic analysis that can be used to assess the feasibility of a business. The business is feasible if the income value is greater than the BEP value. The vision of the Food Science and Technologies Program is "In the year 2022, the realization of the Superior Program that produce professional scholars with food technopreneurs based on religious values”. To realize this vision, students must be equipped with the sciences related to entrepreneurship. The problems, there are no courses experienced by first semester students in Food Science and Technologies Program which containing entrepreneurship or business. The purpose of this program is to provide proficions for students to be more prepared in entrepreneurship. Activity material can be used as a reference in accepting entrepreneurial materials in the next semester. Improvement of understanding can be seen from the results of evaluation of post test questionnaires which showed an increase in understanding of 69%. Participants can find out the basic calculation in assessing the condition of a business. The obstacles faced in this activity are the lack of communication between participants and the media in activities. The media is in the form of business products from participants who will be assessed for their condition. The sustainability plan for the activity is that participants of the activity are encouraged to make a business plan that will be discussed and evaluated in the next activity, hold regular and incidental meetings to discuss the problems faced by participants in making a business plan, and assistance for students who already have a business. Assistance can be in the form of labeling in product packaging, improvement in packaging design, assistance with registration of business licenses, and improvement of marketing media for these products.